Good & sweet : a new way to bake with naturally sweet ingredients - Levy, Brian (Chef) (Avery, an imprint of Penguin Random House, 2022)
"Groundbreaking recipes for real desserts-sweetened entirely by fruit and other natural, unexpectedly sweet ingredients-from a pastry cook who's worked at acclaimed restaurants in New York and France"--